BUSINESS ENVIRONMENT - THE CASE OF WESTERN BALKAN COUNTRIES - Zijad Džafić (Economic Review)
This paper investigates and compares development of the Entrepreneurship and Small and Medium-sized Enterprises (SMEs) sector and different obstacles for development of this sector in the Western Balkan countries (WBCs). Many evidence from the countries of central Europe show that the development of SMEs and entrepreneurship is a key factor for a successful transformation from command to market based economy in WBCs. SMEs create new jobs, products and services, help in restructuring former state enterprises, which is very important for transition countries, and generate government revenues. Also, SMEs stimulate private ownership and entrepreneurial skills and innovations. A special accent in this paper is put on many international reports and datasets relevant to the assessment of business environment in this region. In this paper, the author uses only some such as: The Global Competitiveness Report of World Economic Forum, World Bank’s Doing Business Index, Heritage Foundation's Index of Economic Freedom, European Charter for Small Enterprises and Small Business Act of OECD and European Commission (EC) and Indicators of Business, Corruption and Crime in WBCs of the United Nations Office on Drugs and Crime (UNODC). The author has come to the conclusion that, in respect of SMEs, WBCs lag behind the countries in the European Union. This article aims to analyze the system of regulation and administrative facilitation aspects of doing business in the above mentioned countries and, whether or not this system stimulates, the development of private SMEs and entrepreneurship.